Pelatihan Pengelolaan dan Regulasi Emosi bagi Guru SMK Muhammadiyah 1 Palembang untuk Meningkatkan Kesejahteraan Emosional - Mahmud Junianto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Teachers face complex emotional challenges in the workplace, particularly when dealing with the dynamic nature of Generation Z students. Without adequate emotional regulation skills, teachers are at risk of prolonged stress and burnout. This community service activity aims to improve teachers' emotional regulation skills through training based on Gross's (2003) theory, which includes techniques for recognizing, managing, and responding to emotions adaptively. The activity was conducted at SMK Muhammadiyah 1 Palembang and attended by 30 teachers. The training method included delivering material and practicing emotional regulation in six structured sessions. Results showed that participants were enthusiastic, actively engaged in the practice, and acknowledged their increased understanding and skills in managing negative emotions. Participant reflections indicated that the training helped maintain mental health and increased readiness to face work pressure. In addition, the sessions fostered a supportive environment where teachers could share their emotional experiences and develop mutual empathy. Feedback from participants emphasized the relevance of emotional regulation in daily teaching tasks, including classroom management, dealing with students’ behavior, and interacting with colleagues and parents. However, challenges remain in implementing emotional regulation due to minimal institutional support and limited follow-up programs. Therefore, it is important for this type of training to be integrated into teacher professional development programs and supported by school policies. This activity demonstrates that strengthening teachers' emotional aspects is a strategic step in improving the overall quality of education. Future efforts should involve collaboration with school leadership to institutionalize emotional support mechanisms and conduct longitudinal evaluations to measure sustained impact. Overall, the training offers a promising model for enhancing teacher well-being and professional resilience in demanding educational environments.